Pengaruh Pelayanan Dan Fasilitas Terhadap Kepuasan Pengunjung: Studi Kasus Pada Bayak Hotel Cipayung & Resort - Yuwantiningrum, Sri Endah; Nurdiawanty, Siva Putri (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The growing business competition in Indonesia is a phenomenon that attracts attention to be examined. One of them is in the hotel industry which is one of the service fields that moves by combining products and services. The purpose of the study was to analyze the effect of employee and facility services on visitor satisfaction at Bayak Hotel And Resort.Sampling was carried out by purposive sampling based on the criteria obtained a sample of 100 respondents visitors to Bayak Hotel And Resort. The data source uses primary data. The analysis method uses Validity and Reliability, Multiple linear regression analysis, Classical Assumption Test and Hypothesis Test using IBM SPSS 25 program. The results of this study show that Karaywan Services have an effect on Visitor Satisfaction and Facilities have no effect on Visitor Satisfaction. This research is a consideration for Bayak Hotel And Resort to be able to improve Karaywan and Fasiltias Services in order to increase visitor satisfaction. Keyword: Store Atmosphere, Product Quality,Consumer Satisfaction